Pooling, Pricing and Trading of Risks - Sjur Didrik Flåm (Center for Economic Studies and ifo Institute (CESifo), 2002)
Exchange of risks is considered here as a transferable-utility cooperative game. When the concerned agents are risk averse, there is a core imputation given by means of shadow prices on state-dependent claims. Like in finance, a risk can hardly be evaluated merely by its inherent statistical properties (in isolation from other risks). Rather, evaluation depends on the pooled risk and the convolution of individual preferences. Explored below are relations to finance with some emphasis on incompleteness. Included is a process of bilateral trade which converges to a price-supported core allocation.
Keywords: 330